Where Is the Action in Perception? An Exploratory Study With a Haptic Sensory Substitution Device - Froese, Tom; Ortiz-Garin, Guillermo U. (Frontiers in Psychology, 2020)
Enactive cognitive science (ECS) and ecological psychology (EP) agree that movement is important for perception, but they disagree on the role of agency. EP has focused on the notion of sensorimotor invariants, according to which bodily movements play an instrumental role in perception. ECS has focused on the notion of sensorimotor contingencies, which goes beyond an instrumental role because skillfully regulated movements are claimed to play a constitutive role. We refer to these competing hypotheses as agency invariance and agency contingency, respectively. Evidence comes from a variety of fields, including neural, behavioral, and phenomenological research, but so far with confounds that prevent an experimental resolution. Here we advance the debate by proposing a novel double-participant setup that aims to isolate agency as the key variable that distinguishes bodily movement in active and passive conditions of perception. We pilot this setup in an exploratory psychological study of width discrimination using the Enactive Torch, a haptic sensory substitution device. There was no evidence favoring agency contingency over agency invariance. However, we caution that during debriefing several participants reported using cognitive strategies that did not rely on spatial perception. We conclude that this approach is a viable direction for future research, but that greater care is required to establish and confirm the desired modality of first-person experience.